Simplify the expressions and find the value if x is equal to 2

(i) x + 7 + 4(x-5)

(ii) 3(x+2) + 5x-7

(iii) 6x + 5(x-2)

(iv) 4(2x-1) + 3x +11

(i) x + 7 + 4(x - 5)

= x + 7 + 4x - 20

= x + 4x + 7 - 20

= 5x - 13

Put x = 2

= 5(2) - 13

= 10 - 13

= -3

(ii)3(x+2) + 5x - 7

= 3x + 6 + 5x - 7

= 3x + 5x + 6 - 7

= 8x - 1

Put x = 2

= 8(2) - 1

= 16 - 1

= 15

(iii) 6x + 5(x - 2)

= 6x + 5x - 10

= 11x - 10

Put x = 2

= 11(2) - 10

= 22 - 10

= 12

(iv) 4(2x - 1) + 3x + 11

= 8x - 4 + 3x + 11

= 8x + 3x -4 + 11

= 11x + 7

Put x = 2

=11(2) + 7

= 22 + 7

= 29

14